Analisis Pengaruh Dana Pihak Ketiga (DPK), Non Performing Financing (NPF), Bi Rate, dan Capital Adequacy Ratio (CAR) Terhadap Penyaluran Pembiayaan Pada Bank Umum Syariah di Indonesia Periode 2011-2015 - Saba, Sabarudin (Bisei : Jurnal Bisnis dan Ekonomi Islam, 2021)
Abstrack: The aims of this research are to analyze the influence of Third Party Fund (DPK), Non Performing Financing (NPF), the BI Rate and Capital Adequacy Ratio (CAR) partially and simultaneously to the Distribution Financing Islamic Banks in Indonesia 2011-2015. The population in this research is all Islamic Banks in Indonesia in Period 2011-2015. This research uses purposive sampling method. The amount of sample in this research is 5 (five) Islamic Banks. The analysis model uses panel data reggresion model and analysis techniques techniques to the hypothesis uses Ftest,t-test, and R2 test.The results in this research in Third Party Fund (DPK) partially has positive andsignificant effect to Financing Distribution of Islamic Banks in Indonesia in Period 2011-2015, Ratio of Non-Performing Financing (NPF) partially negative and not significant to Distribution Financing Islamic Banks in Indonesia in Period 2011-2015, BI Rate is partially positive and significant to FinancingDistribution of Islamic Banks in Indonesia period 2011-2015, and the ratio of Capital Adequacy ratio (CAR) partially negative and significant to FinancingDistribution of Islamic Banks in Indonesia 2011-2015 , Simultaneously ThirdParty Fund (DPK), Non Performing Financing (NPF), the BI Rate and Capital Adequacy Ratio (CAR) have significant effect to Financing Distribution of Islamic Banks in Indonesia 2011-2015.